2007
DOI: 10.1080/14786410701571384
|View full text |Cite
|
Sign up to set email alerts
|

Endemic species of sardo-corso-balearic area: molecular composition and biological assay of Teucrium

Abstract: Teucrium marum and T. subspinosum have been extracted with different polarity solvents, each crude extract was analysed with (1)H-NMR to compare the overall metabolic component. The polar extracts showed antioxidant activity in vitro. Verbascoside and arabinosyl-verbascoside were isolated and identified. Their concentrations were in connection to the antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…It is represented by herbs or shrubs, with tubular or campanulate calyx, 2-lipped or actinomorphic, 5-toothed, the teeth equal or the upper larger; corolla with one 5-lobed lip; tube without a ring of hairs inside, often included in the calyx; and nutlets smooth or reticulate. Many taxa of the genus Teucrium have been used in traditional medicine as stimulants, tonics, and stomach-ache remedies, for their antioxidant, antifungal, antibacterial, antidiabetic, antiseptic, astringent, antispasmodic, anti-inflammatory, antianemic, and cicatrizant properties, and to treat skin diseases [ 3 , 4 , 5 , 6 , 7 ]. Phytochemical studies reported the presence of both volatile and non-volatile compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is represented by herbs or shrubs, with tubular or campanulate calyx, 2-lipped or actinomorphic, 5-toothed, the teeth equal or the upper larger; corolla with one 5-lobed lip; tube without a ring of hairs inside, often included in the calyx; and nutlets smooth or reticulate. Many taxa of the genus Teucrium have been used in traditional medicine as stimulants, tonics, and stomach-ache remedies, for their antioxidant, antifungal, antibacterial, antidiabetic, antiseptic, astringent, antispasmodic, anti-inflammatory, antianemic, and cicatrizant properties, and to treat skin diseases [ 3 , 4 , 5 , 6 , 7 ]. Phytochemical studies reported the presence of both volatile and non-volatile compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies reported the presence of both volatile and non-volatile compounds. Of the latter, several neo-clerodane diterpenoids were isolated and considered as chemotaxonomic markers of the genus [ 4 , 8 , 9 , 10 ], along with iridoids, sesquiterpenes, triterpenes, abietane diterpenes, flavonoids, and other classes of specialized metabolites [ 11 ]. Much scientific research has already been carried out on essential oils (EOs), since 99 Teucrium taxa have been investigated to date [ 7 ], highlighting the main volatile compounds, which are generally sesquiterpene hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…T. marum is a small, perennial, suffrutic, bushy and evergreen plant that grows in height after 30–40 cm high. The thin branches of this highly aromatic plant are covered with thick white down …”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of T. marum has been the subject of numerous studies in which phenylpropanoid, neo‐clerodane diterpenoids and iridoid cyclopentane monoterpenes have been reported. Iridoids such as dolichodial, teucrein and dolicholactone are volatile components of T. marum identified in the organic solvent extracts obtained by Soxhlet and simultaneous distillation–extraction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation